A comparison between analogic and digital media in Engineering teaching (Acta Scientiarum. Education, 2021)
Form representation is essential for any area that involves the creation of artefacts, since without it the project is just an idea in the mental field. In general terms, it is the ability to perceive and understand shapes and represent them through perspectives and orthographic views, as well as through models and geometric models. Given the issues raised, it is possible to understand the importance of knowledge related to the graphic representation of architecture for professionals involved with the Aeco Industry (Architecture, Engineering, Construction and Operation) and, also the relevance of graphic geometry disciplines on the development of Visiographic Three-dimensional Capacity. So, this paper aims to investigate the impact caused by the use of traditional and digital media in the teaching of graphic representation. To this end, two groups of students were compared, one exposed to the use of both media - analogic and digital - and another that used just digital media. From the application of questionnaires, it was possible to identify the student’s profile, their preferences of media and difficulties encountered. The work presumes that students exposed to more disciplines of graphic geometry will have less difficulties compared to those who had less contact. The main results indicated that: there is a preference, in both groups, for digital media to perform practical activities; the need to adapt the content to each specific engineering and that the most significant difficulties were related to work management, regardless of the media used.